Effects of the Pesticides Benomyl, Metribuzin and Imidacloprid on Soil Microbial Communities in the Field - Rostislav Streletskii; Angelika Astaykina; Vladimir Cheptsov; Andrey Belov; Victor Gorbatov (Agriculture, 2023)
Pesticide preparations based on benomyl, metribuzin and imidacloprid were used on a potato plot for three years. Every year soil samples were taken at 0, 7, 14, 28, 56 and 84 days after treatment. For all samples, the pesticide residues in the soil were measured. A study of the soil’s bacterial and fungal community structures was preformed using next-generation sequencing. It was found that the rate of decomposition of the pesticides increased every year, while the pesticides affected only certain phylogenetic groups of microorganisms. The most significant effect was the decrease in the proportion of Ascomycota. Additionally, in the field, as well as previously in the laboratory, pesticides have had an impact on the relative abundance of the genera Haliangium, Solicoccozyma and Humicola. It can be assumed that the repeated application of pesticides does not have a significant effect on the microbial communities of soils, provided that they are applied according to the application rate.